Factors Involved in Estimating Cost of Email Spam - Ridzuan, Farida; Potdar, Vidyasagar; Talevski, Alex (Springer, 2010)
This paper analyses existing research work to identify all possible factors involved in estimating cost of spam. Main motivation of this paper is to provide unbiased spam costs estimation. For that, we first study the email spam lifecycle and identify all possible stakeholders. We then categorise cost and study the impact on each stakeholder. This initial study will form the backbone of the real time spam cost calculating engine that we are developing for Australia.